Coshaping Digital and Biological Animals: Companion Species Encounters and Biopower in the Video Games Pikmin and Pokémon - Attebery, Stina (Humanimalia, 2015)
This paper considers how video games featuring animals as biological resources are simulating the types of “messy coshapings” that Donna Haraway values in companion species relationships, despite relocating these coshapings to a digital environment. The two game franchises that I am using for this argument—Pikmin and Pokémon—feature animal-like digital creatures who can be situated alongside biological animals through their imbrication in similar biopolitical structures of pet ownership, breeding and genetic manipulation, and animal training. I argue that embodied relationships of dominance and biopower become recoded in these digital spaces through a process similar to Eugene Thacker’s “biological exchanges,” where biology becomes both material and immaterial through processes like bioinformatics. In these two game worlds, biological exchanges occur through the tension between the player’s instrumentalization of animal biopower and the depiction of these creatures as affective and vulnerable. By emphasizing the vulnerability of digital animals under a system of biopower, Pikmin and Pokémon invite the player to decode her experiences managing immaterial, digital animal populations in order to rethink her relationships with embodied, biological animals.